Studying the Utility of Using Reed and Sawdust as Waste Materials to Produce Cementitious Building Units (Journal of Engineering, 2015)
In this research, the possibility of using waste wooden materials (reed and sawdust) was studied to produce sustainable and thermal insulation lightweight building units , which has economic and environmental advantages. This study is intended to produce light weight building units with low thermal conductivity, so it can be used as partitions to improve the thermal insulation in buildings. Waste wooden materials were used as a partial replacement of natural sand, in different percentages (10, 20, 30, and 40) % . The mix proportions were (1:2.5) (cement: fine aggregate) with w/c of 0.4. The values of 28 days oven dry density ranged between (2060-1693) kg/m3.The thermal conductivity decreased from (0.745 to 0.222) W/m. K .The percentages of decrease in 28 days compressive strength were (30.8, 36.8, 50 and 56.4) % .The flexural strength increased at low replacement of reed and sawdust content, and then it decreases with the increase of reed and sawdust content. At the end of the work, building units were produced from selected mix (natural sand with 30 % reed and sawdust) (MS30) .Two types of brick units were produced; the first type without coating reed or sawdust and the second type was coated with bituminous emulsion. The coating with bituminous emulsion increased the compressive by about (20.3) % and the water absorption was reduced by about (30.4) %. Efflorescence was almost negligible for both types of bricks.